2020
DOI: 10.1111/fcp.12544
|View full text |Cite
|
Sign up to set email alerts
|

Psychotropic drug initiation in patients diagnosed with chronic myeloid leukemia: a population‐based study in France

Abstract: Psychotropic drugs (PD) are often used close to a cancer diagnosis and may be considered as a way of coping. We aimed to determine the incidence of anxiolytics, hypnotics, antidepressants, and antipsychotics initiation around a diagnosis of chronic myelogenous leukemia (CML). Population‐based cohort: Data were extracted from Systeme National des données de Santé (SNDS, the French health insurance database) at the regional level (Midi‐Pyrenees area, 2.9 million inhabitants). All newly diagnosed patients treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 48 publications
(61 reference statements)
1
9
1
Order By: Relevance
“…Multiple non‐U.S. cancer studies have also observed this class to be the most frequently prescribed 23–29 . However, we observed remarkably lower rates of prescription compared to available studies.…”
Section: Discussioncontrasting
confidence: 63%
See 3 more Smart Citations
“…Multiple non‐U.S. cancer studies have also observed this class to be the most frequently prescribed 23–29 . However, we observed remarkably lower rates of prescription compared to available studies.…”
Section: Discussioncontrasting
confidence: 63%
“…A national cohort study in France found a 20% increase in PD prescription rates following a cancer diagnosis 27 . Another French study 28 and a Dutch case–control of multiple cancers 29 reported rates of 32%–33%. A Scottish case–control study found cancer patients to have 10 times more PD prescriptions than that of the general population 30 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We used a specific algorithm to identify incident CML patients who were treated between 1 January 2011 (in order to have at least 12 months before TKI initiation for the identification of comorbidities) and 31 December 2014 (to have at least 12 months of follow-up for the last patients included, to investigate patterns of TKI utilization). The initial algorithm was previously used in a pilot study based on regional data extracted from the SNDS ( 27 ).…”
Section: Methodsmentioning
confidence: 99%